2015
DOI: 10.5120/20148-2280
|View full text |Cite
|
Sign up to set email alerts
|

Removal of High Density Impulse Noise using Efficient Median Filter for Digital Image

Abstract: An Efficient Median Filter (EMF) algorithm for removal or enhancement of gray scale images are highly corrupted impulse noise is proposed in this paper. Noise in image are represent the pixel value 0's and 255's are ensures that black and white dot in image. In proposed algorithm take an image and select 3x3 size window and target or center pixel value check if its value is 0's or 255's then image is corrupted otherwise noise free image. If image is noisy and target pixels neighboring pixel value is between 0'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Noise filtering is one of the pre-processing steps in every digital image processing technique. A median filter is a popular noise filter which is used to remove salt and pepper noise in digital images [16][17][18][19] . It has been reported that impulse noise in high-density noisy images can be effectively removed by using an improved algorithm such as a decision based adaptive neighborhood median filter [20].…”
Section: Introductionmentioning
confidence: 99%
“…Noise filtering is one of the pre-processing steps in every digital image processing technique. A median filter is a popular noise filter which is used to remove salt and pepper noise in digital images [16][17][18][19] . It has been reported that impulse noise in high-density noisy images can be effectively removed by using an improved algorithm such as a decision based adaptive neighborhood median filter [20].…”
Section: Introductionmentioning
confidence: 99%